Aristolactam-type alkaloids from orophea enterocarpa and their cytotoxicities - Sanchai Nayyatip (2018)
A new aristolactam, named enterocarpam-III (10-amino-2,3,4,6-tetramethoxy phenanthrene-1-carboxylic acid lactam, 1) together with the known alkaloid stigmalactam (2), were isolated from Orophea enterocarpa. Their structures were elucidated on the basis of interpretation of their spectroscopic data. Compounds 1 and 2 exhibited significant cytotoxicities against human colon adenocarcinoma (HCT15) cell line with IC50 values of 1.68 and 1.32 μM, respectively. © 2012 by the authors.